Recent Applications on Dual-Catalysis for C–C and C–X Cross-Coupling Reactions - Ravi Kishore, Dakoju; Sreenivasulu, Chinnabattigalla; Dapkekar, Anil Balajirao; Satyanarayana, Gedu (SynOpen, 2022)
Coupling reactions stand amid the most significant reactions in synthetic organic chemistry. Of late, these coupling strategies are being viewed as a versatile synthetic tool for a wide range of organic transformations in many sectors of chemistry, ranging from indispensable synthetic scaffolds and natural products of biological significance to novel organic materials. Further, the use of dual-catalysis in accomplishing various interesting cross-coupling transformations is an emerging field in synthetic organic chemistry, owing to their high catalytic performance rather than the use of a single catalyst. In recent years, synthetic organic chemists have given considerable attention to hetero-dual catalysis; wherein these catalytic systems have been employed for the construction of versatile carbon–carbon [C(sp3)–C(sp3), C(sp3)–C(sp2), C(sp2)–C(sp2)] and carbon–heteroatom (C–N, C–O, C–P, C–S) bonds. Therefore, in this mini-review, we are emphasizing recently developed various cross-coupling reactions catalysed by transition-metal dual-catalysis (i.e., using palladium and copper catalysts, but omitting the reports on photoredox/metal catalysis).1 Introduction2 Cu/Pd-Catalysed Bond Formation2.1 Pd/Cu-Catalysed C(sp3)–C(sp2) Bond Formation2.2 Pd/Cu-Catalysed C(sp2)–C(sp2) Bond Formation2.3 Pd/Cu-Catalysed C(sp)–C(sp2) Bond Formation2.4 Pd/Cu-Catalysed C(sp3)–C(sp3) Bond Formation2.5 Pd/Cu-Catalysed C–X (X = B, N, P, S, Si) Bond Formation3 Conclusion
Keywords: dual-metal catalysis; cross-coupling reactions; Kinugasa reaction; palladium catalysis; heterocycles